What affects the placebo effect?. (March 2020) - Baines, Georgina; Araklitis, George; Flint, Richard; Robinson, Dudley; Cardozo, Linda
Abstract: Objective: To determine whether electronic bladder diaries are associated with a larger placebo effect than paper diaries in studies of overactive bladder (OAB). To identify any other factors in study design that may influence the placebo effect. Study design: This is a secondary analysis of a previous systematic review and network meta-analysis on the efficacy and tolerability of mirabegron. Each study was analysed and placebo response rate (PRR) was calculated. Statistical analysis was used to look for associations with different factors and PRR. Results: The PRR was considerable in the studies analysed (10.5 % when calculated for change in number of micturitions over 24 h and 41.2 % for change in urgency urinary incontinence episodes over 24 h). Paper bladder diaries were associated with a significantly larger placebo response rate than electronic (10.76 % vs 10.22 %), although this may be clinically small. The size of study had a moderate positive correlation with PRR. Length of bladder diary was not associated with increased PRR. Conclusions: The PRR in studies of OAB is varied and significant. It is clear that it can be affected by factors in study design including type of bladder diary. When designing clinical studies this should be borne in mind. Equally, when attempting to optimise patient care, the benefit of the therapeutic encounter should be remembered.